2010
DOI: 10.1016/j.humov.2010.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of the Fouetté turn

Abstract: The Fouetté turn in classical ballet is performed repeatedly on one leg with swinging of the free limbs, producing a continued sequence of turns with one turn leading into the next. The purpose of this study was to determine the possible time history profiles of the twisting torque between the supporting leg and the remainder of the body that will allow continued performances of the Fouetté turn. Simulations were performed using a model which comprised the supporting leg and the remainder of the body to find t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 3 publications
1
10
0
1
Order By: Relevance
“…During a piqué turn, applying a moment about a translating center of mass is particularly challenging because the desired translation is greater than it is during a pirouette and the turn is initiated with single leg support. During single-leg support phases of fouetté turns, study of the ground reaction forces revealed a large contribution of the free moment towards generating angular impulse at a time that the CM horizontal position is close to the center of pressure (Imura & Yeadon, 2010). In the pique turn, the CM translates from its initial CM horizontal proximity to the center of pressure, which could provide an opportunity to use the horizontal reaction force (RFh) to apply a moment about the CM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During a piqué turn, applying a moment about a translating center of mass is particularly challenging because the desired translation is greater than it is during a pirouette and the turn is initiated with single leg support. During single-leg support phases of fouetté turns, study of the ground reaction forces revealed a large contribution of the free moment towards generating angular impulse at a time that the CM horizontal position is close to the center of pressure (Imura & Yeadon, 2010). In the pique turn, the CM translates from its initial CM horizontal proximity to the center of pressure, which could provide an opportunity to use the horizontal reaction force (RFh) to apply a moment about the CM.…”
Section: Introductionmentioning
confidence: 99%
“…Studying the piqué turn also provides an opportunity to identify strategies used to accommodate increased rotational demands. Though subsystem momentum and initial stance configuration were previously studied in pirouettes with increased rotational demand (Imura & Yeadon, 2010;Kim et al, 2014;Sugano & Laws, 2002), the role of each leg towards linear and angular impulse generation has not been identified, despite its implications to help dance training. In a cutting maneuver with increased rotational demands, as moment of inertia about a vertical axis increased, the horizontal reaction force (RFh) did not change direction relative to the support leg and the RFh magnitude perpendicular to the CM advancement direction generally increased when the phase duration was similar (Qiao, Brown, & Jindrich, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic balance of ballet dancers was assessed by a few authors, and the execution of spins (pirouette) was considered as a complex task, involving a strategy of head movement, the "marking the head", which dissociates the rotation of trunk and head -while the body spins, the eyes stare at an established point, and when the maximal cervical rotation is reached, the head performs a fast rotation towards the same direction of the movement, and then the eyes stare at the same point again; therefore, it is possible to observe the importance of visual information for balance and quality of the motor performance during the spin, correlated to less postural oscillation 8,[13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Imura and Yeadon (2010) developed a simulation model that incorporated both sliding and stiction when representing the frictional forces between the floor and a dancer's foot during a Fouetté turn in ballet. Within Imura and Yeadon's model the dancer was modelled using only two segments which greatly simplified the system and limited the extent to which the model results could be compared to recorded movements.…”
Section: Introductionmentioning
confidence: 99%